Effects of regional context and landscape composition on diversity and composition of small rodent assemblages in Argentinian temperate grasslands and wetlands - Massa, Carolina (2014)
This study aims to describe landscape evolution in two contiguous ecoregions with different land use intensity, to assess changes in small mammal assemblages. Rodent remains in pellet samples from barn owls were used to estimate the attributes of rodent assemblages. Two major biomes were considered in this study, a mosaic of wetlands (Delta and Paran á Islands ecoregion) and a mosaic of grasslands and cultivated fields (Pampa ecoregion). Environmental characterization was based on the analysis of satellite images and weather data. Fourteen rodent species in 28 sampling sites were identified, totaling 7645 prey items. Linear combinations of variables that characterized the landscape explained 66.6% of variation in the composition of rodent assemblages. A positive linear relationship between rodent diversity and the number of different patches was found in the Pampa. Our results suggest that landscape disturbances caused by agricultural intensification favor the increase of generalist and competitively subordinated species. In turn, changes in rodent diversity at the Paran á Delta were negatively associated with the percentage of water-covered area and the number of patches. The hydrological regime of this ecoregion acts as a filter for species establishment, restricting the richness of the rodent assemblages.